Foreign Investor Flows and Sovereign Bond Yields in Advanced Economies - Serkan Arslanalp; Tigran Poghosyan (Journal of Banking and Financial Economics)
Asset allocation decisions of international investors are at the core of capital fl ows. This paper explores the impact of these decisions on long-term government bond yields, using a quarterly investor base dataset for 22 advanced economies over 2004‒2012. We fi nd that a one percentage point increase in the share of government debt held by foreign investors can explain a 6‒10 basis point reduction in long-term sovereign bond yields over the sample period. Accordingly, international fl ows to core advanced economy bond markets over 2008‒12 are estimated to have reduced 10-year government bond yields by 40‒65 basis points in Germany, 20‒30 basis points in the U.K., and 35‒60 basis points in the U.S. In contrast, foreign outfl ows are estimated to have raised 10-year government bond yields by 40‒70 basis points in Italy and 110‒180 basis points in Spain during the same period. These results suggest that changes in the foreign investor base for sovereign debt can have economically and statistically signifi cant effects on sovereign bond yields, independent of other standard macroeconomic determinants of bond yields.